Four riders of the apocalypse of the Polish bureaucracy - Witold Kieżun (Foundations of Management, 2018)
This article was originally published in Polish as: Witold Kieçzun, Czterej jezdzcy apokalipsy polskiej biurokracji, Kultura, No. 3/630, Paris 2000. The Literary Institute (publisher of the 'Kultura' monthly) expressed its interest in and consent to the publication of an English-language version of this article. Professor Witold Kieçzun also gave his consent to the translation of his text and its posting in the pages of the journal Foundations of Management. The text was written in 1999 and introduced subsequent to January 1 of that year, regarding the reform of the administrative division of Poland, which involved, among other things, three-stage structure of territorial division and the introduction of counties as administrative units (editorial note).
Keywords: 650; arrogance of power bureaucracy; corruption; gigantomania; luxuryomania; pathology; praxeology; public administration